Implikasi Pasal 97 Undang-Undang No 1 Tahun 2022 Tentang HKPD terhadap Desentralisasi Fiskal : Implications of Article 97 of Law No. 1 of 2022 concerning HKPD on Fiscal Decentralization - Saputra, Andi; Rachmad Soetijono, Iwan; Listyana Chandra, Ratih (UIN Kiai Haji Ahmad Sidiq Jember, 2025)
Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments has shifted the direction of Indonesia's fiscal decentralization toward a more centralized approac Although formal regional autonomy remains in effect, regional fiscal dependence on the central government remains hig This centralization is further clarified through Article 97 of the Regional Government Regulation (HKPD), which authorizes the central government to revoke regional regulations regarding tax and levy rates if deemed inconsistent with national strategic programs. This approach has generated dynamics and resistance, including from the Prosperous Justice Party (PKS) faction, which believes the HKPD Law does not reflect fiscal justice, minimizes public participation, and has the potential to increase the tax burden. Furthermore, the implementation of a closed list system for types of taxes and levies further limits regional fiscal space and contradicts the principles of regional autonomy. Abstrak Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan antara Pemerintah Pusat dan Pemerintah Daerah mengubah arah desentralisasi fiskal Indonesia menjadi lebih sentralistik. Meskipun otonomi daerah secara formal masih berlaku, ketergantungan fiskal daerah terhadap pusat tetap tinggi. Sentralisasi makin nyata melalui Pasal 97 UU HKPD, yang memberi kewenangan kepada pemerintah pusat untuk membatalkan peraturan daerah terkait tarif pajak dan retribusi apabila dianggap tidak sejalan dengan program strategis nasional. Pendekatan ini memunculkan dinamika dan resistensi, termasuk dari Fraksi PKS yang menilai UU HKPD tidak mencerminkan keadilan fiskal, minim partisipasi publik, serta berpotensi menambah beban pajak. Selain itu, penerapan sistem closed list atas jenis pajak dan retribusi semakin membatasi ruang fiskal daerah dan bertentangan dengan prinsip otonomi daerah.